State-Owned Multinationals Governments in Global Business (JIBS Special Collections,, 2018)
This book provides a deep understanding of state-owned multinationals (SOMNCs) and their role in global business. SOMNCs have emerged as a force to contend with in global competition, and their study connects several fields such as economics, political economy, international business and global strategy. This prestigious collection of articles presents insights into the interaction between government ownership and internationalization, and aims to provoke new research approaches and insights on the topic. The book includes some of the key contributions to our understanding of these firms and new commentaries explaining how to analyze them. This book is essential reading for academics and consultants looking to gain a clearer understanding of SOMNCs and how to research them.